Development of a new electrochemical sensor based on silver sulfide nanoparticles and hierarchical porous carbon modified carbon paste electrode for determination of cyanide in river water samples - Cárdenas Riojas A.A. (2019)
In this study, a new electrochemical sensor for determination of cyanide is proposed. The sensor is formed by a carbon paste electrode modified with hierarchical porous carbon and silver sulfide nanoparticles. The morphology characterization was performed by transmission electron microscopy (TEM) and scanning electron microscopy (SEM), while the chemical and electrochemistry characterization were performed by energy dispersive X-ray spectroscopy and cyclic voltammetry, respectively. Under the optimized conditions, the Ag2SNPs-HPC300 sensor presented a large concentration linear range of 5.9 × 10−7 to 1.1 × 10-3 mol L-1, and limit of detection of 7.0 × 10-8 mol L-1 using square-wave adsorptive anodic stripping voltammetry (SWAdASV) technique. The analytical response of the Ag2SNPs-HPC300 sensor was evaluated in presence of different compounds, and the results showed a RSD of 4.3% in triplicate experiments. The applicability of the Ag2SNPs-HPC300 sensor in river water samples contaminated with cyanine showed recoveries values near 100%. The developed method exhibited high sensitivity and selectivity, good reproducibility, repeatability and low-cost, demonstrating to be a very promising analytical alternative for determination of cyanide in this matrix.